The Texas Quail Index: Evaluating Predictors of Northern Bobwhite Productivity and Abundance Using Citizen Science - Kelly S. Reyna; Dale Rollins; Dean Ransom Jr. (National Quail Symposium Proceedings, 2017)
Annual abundance of northern bobwhites (Colinus virginianus) fluctuates drastically in semi-arid environments (e.g., Texas), which complicates the ability of wildlife biologists and quail managers to predict annual bobwhite productivity and relative abundance for the ensuing hunting season. The Texas Quail Index (TQI) was a 5-year citizen science project that evaluated several indices as predictors of bobwhite productivity and abundance during the subsequent fall. Indices included spring cock-call counts, forb species richness, simulated-nest fate, potential nest-site density, scent station visitation rates, roadside counts, fall covey call counts, and harvest data. Spring cock-call counts explained only 41% of the variation in fall bobwhite abundance across all study sites in years 1–4; yet explained 89% of the variation in year 5. The percentage of juveniles in the fall population (an index of bobwhite productivity) was significantly lower in year 5. All study sites experienced drought conditions throughout year 5 based on the Palmer Drought Severity Index (PDSI). Thus, drought conditions in semi-arid environments result in reduced productivity compared to non-drought years. Our results suggest low recruitment during drought years makes fall bobwhite abundance more predictable than during non-drought years. Wildlife biologists and quail managers should have a better ability to predict bobwhite productivity and fall abundance in drought years by recording spring cock-call counts.
Keywords: call counts; citizen science; Colinus virginianus; density estimate; northern bobwhite; population dynamics; predators; quail abundance; reproduction; Texas